Leaning against the wind: Macroprudential policy and the financial cycle - Thore Kockerols; Christoffer Kok Sørensen (European Central Bank (ECB), 2019)
Should monetary policy lean against financial stability risks? This has been a subject of fierce debate over the last decades. We contribute to the debate about "leaning against the wind" (LAW) along three lines. First, we evaluate the cost and benefits of LAW using the Svensson (2017) framework for the euro area and find that the costs outweigh the benefits. Second, we extend the framework to address a critique that Svensson does not consider the lower frequency financial cycle. Third, we use this extended framework to assess the costs and benefits of monetary and macroprudential policy. We find that macroprudential policy has net marginal benefits in addressing risks to financial stability in the euro area, whereas monetary policy has net marginal costs. This would suggest that an active use of macroprudential policies targeting financial stability risks would alleviate the burden on monetary policy to "lean against the wind".
Keywords: E58; G01; 330; leaning against the wind; macroprudential policy; financial cycle